Using input-output analysis framework to explain economic diversification and structural transformation in Bangladesh - Valerie Mercer-Blackman; Amador Foronda; Joseph Mariasingham (Asian Development Bank (ADB), 2017)
Existing literature on economic growth and structural change relies on trade data to make pronouncements about a country's competitiveness and long-term growth prospects through the acquisition of capabilities. However, insufficient data give us a limited view of what is happening within the domestic economy, and how the development of manufacturing through links in the production process leads to the export of intermediate or final products. Using input-output data, this paper devises an agglomeration indicator to measure economic diversification and to compare Bangladesh with other key economies. In the process, we shed light on the symbiotic relationship between manufacturing and services as the country develops. Despite Bangladesh's astounding growth over the past 15 years, diversification has been somewhat slower than expected for its level of development.
Keywords: D24; D57; F15; O14; 330; Bangladesh; business services; economic diversification; global value chains; input-output tables; ready-made garments; structural transformation